ICOS-Fc as innovative immunomodulatory approach to counteract inflammation and organ injury in sepsis - Alves, Gustavo Ferreira; Stoppa, Ian; Aimaretti, Eleonora; Monge, Chiara; Mastrocola, Raffaella; Porchietto, Elisa; Einaudi, Giacomo; Collotta, Debora; Bertocchi, Ilaria; Boggio, Elena; Gigliotti, Casimiro Luca; Clemente, Nausicaa; et al. (Frontiers in Immunology, 2022)
Inducible T cell co-stimulator (ICOS), a costimulatory immune checkpoint expressed on activated T cells and its ligand, ICOSL, which is expressed on antigen-presenting cells and non-hematopoietic cells, have been extensively investigated in the immune response. Recent findings showed that a soluble recombinant form of ICOS (ICOS-Fc) can act as an innovative immunomodulatory drug as both antagonist of ICOS and agonist of ICOSL, modulating cytokine release and cell migration to inflamed tissues. Although the ICOS-ICOSL pathway has been poorly investigated in the septic context, a few studies have reported that septic patients have reduced ICOS expression in whole blood and increased serum levels of osteopontin (OPN), that is another ligand of ICOSL. Thus, we investigated the role of the ICOS-ICOSL axis in the pathogenesis of sepsis and the potential beneficial effects of immunomodulation by administering ICOS-Fc in a murine model of sepsis. Five-month-old male wild-type (WT) C57BL/6, ICOS-/-, ICOSL-/- and OPN-/- mice underwent either CLP or Sham surgery and 1 h after the surgical procedure, mice were randomly assigned to receive once ICOS-Fc, F119SICOS-Fc, a mutated form uncapable to bind ICOSL, or vehicle intravenously. Organs and plasma were collected 24 h after surgery for analyses. When compared to Sham mice, WT mice subjected to CLP developed within 24 h a higher clinical severity score, a reduced body temperature, an increase in plasma cytokines (TNF-α, IL-1β, IL-6, IFN-γ and IL-10), liver injury (AST and ALT) and kidney (creatinine and urea) dysfunction. Administration of ICOS-Fc to WT CLP mice reduced all of these abnormalities caused by sepsis. Similar beneficial effects were not seen in CLP-mice treated with F119SICOS-Fc. Treatment of CLP-mice with ICOS-Fc also attenuated the sepsis-induced local activation of FAK, P38 MAPK and NLRP3 inflammasome. ICOS-Fc seemed to act at both sides of the ICOS-ICOSL interaction, as the protective effect was lost in CLP-induced sepsis in knockout mice for the ICOS or ICOSL genes, whereas it was maintained in OPN knockout mice. Taken together, our data show for the first time the beneficial effects of pharmacological modulation of the ICOS-ICOSL pathway in counteracting the sepsis-induced inflammation and organ dysfunction.